Alphaworld: making work easy - Rees, Rod (Oxford University Press Melbourne, 2004)
Making work easy involves finding ways to streamline tasks, enhance productivity, and reduce stress. This can include organizing your workspace to minimize clutter, using tools and technology to automate repetitive tasks, and prioritizing assignments to focus on what's most important. Breaking larger projects into manageable steps can also help make them less overwhelming. Additionally, fostering a collaborative environment and communicating effectively with colleagues can lead to shared solutions and support. By implementing these strategies, work can become more efficient and enjoyable, allowing for greater focus and creativity.